Organizational Climate and Service Quality in the General Services Area of the National University of Jaén - Cruz Chumacero, Diana; Méndez Gutiérrez, Leidy Lucia (LACCEI, 2024)
The objective of the study was to determine the relationship between the organizational climate and the quality of service in the General Services Area of the National University of Jaén (UNJ), through a survey 60 collaborators from the study area were evaluated. The results showed a Spearman's Rho of 0.662 and a bilateral significance of 0.000 < 0.05, indicating that there is a moderate direct correlation between the organizational climate and service quality. Furthermore, it was shown that institutional identity and interpersonal relationships are directly significantly related to the quality of service in the General Services Area of the National University of Jaén, with a moderate coefficient of association equal to 0.664 (r=0.664 ) and 0.580 (r=0.580) respectively, and a bilateral significance 0.000 (ρ < 0.05). It was concluded that a healthy organizational climate leads to improving the quality of service.